The Analysis of Instructional Process through Scientific Approach on Science Subject Matter and Its Effects toward Learning Achievement - Ni Luh Putu Yanti Pratiwi (Journal of Psychology and Instruction, 2017)
This study aim to describe the implementation of a scientific approach in the learning process and know the differences learning outcomes of science in terms of the levels scientific learning process in grade V at SD Negeri 1 Semarapura Tengah. This study was descriptive and inferential, the study population was a learning process in grade V SD Negeri 1 Semarapura Tengah. Samples were taken by eksidental sampling because researchers use science learning process ongoing research in class V SD Negeri 1 Semarapura Tengah is Theme 9 "Environment Our Friends". Data collection methods used were observation, test, and kuesioner. Data collected using an objective test instruments, questionnaires and guidelines for observation and then analyzed using descriptive statistical analysis and inferential statistics (t-test). The study found that the levels scientific learning process science of classr VB obtain an average score of 62 which included a high category and class VC obtain an average score of 47 which included medium category. There are differences in outcomes between students learn science class VB and VC classes. (T = 10.379 and p = 0.000). Because the p-value less than α = 0.05, which means that H0 is rejected can thus be interpreted that there are significant differences between students' learning outcomes science VB and VC classes are taught using a scientific approach. Of the average score obtained, VB class gained an average score of 151.62 which is at a very high category. While the average score obtained VC class is 126.72 which is at a high category.